Bodies of resistance: the dynamic expression of territories in the Amazon multilocal landscapes - Brugnara, Gisela de Andrade (The ESPecialist, 2024)
In the Upper Amazon south of the Solimões River, between valleys, rivers and small towns, a contemporary practice can be observed in the use of ethnic clothing by some indigenous groups, in their life of urban and multi-local extra-village relationships, as an expressive and communicative attitude of multiple senses. This attitude currently forms a context of displacements in a forest-city-forest network, which carry dynamics of cultural resistance and promote the expansion of native territorialities in the city space. In this hostile space, the forest then materializes itself through bodies adorned by colors and designs composed in a syntax unintelligible to Portuguese, making visible what the processes of domination try to extinguish.